Stone's plastic surgery facts : a revision guide - Chiu, Tor Wo (Boca Raton, FL : CRC Press, 2019)
Stone's Plastic Surgery Facts 4e provides a complete revision tool for the FRCS exit examination in plastic surgery. Written in the form of notes and lists, the full range of plastic surgery topics is covered as follows, wound care, burns, head & neck, cleft lip and palate and craniofacial anomalies, breast, hand and upper limb, lower limb, skin and soft tissue tumours, genitourinary and trunk, aesthetic and general plastic surgery. Updated article summaries and a review section in each chapter highlight important points and explain common misconceptions. A vital resource for the surgical trainee.
Includes index.
OCLC-licensed vendor bibliographic record.
Keywords: Surgery, Plastic; MEDICAL / Surgery / General; MEDICAL / Surgery / Plastic & Cosmetic